DESIGN AND DEVELOPMENT OF HALAL INDUSTRY DOCUMENTARY VIDEOS USING MDLC - Tony Wibowo; Dian Putri Manelsi (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Documentary video have been long used to deliver complex message and knowledge in a more concise and easier to consumed format. This format is dominantly used to convey message to older generation, but due to state of global pandemic, younger generation also consuming documentary video as learning media. Current news about Islam might turn off some people to even trying to understand what Islamic culture is due to islamophobia. This study aims to deliver one of Islamic core culture, ‘halal’, in which can be formed in various sectors of industry. We used the MDLC methodology and motion text technique to develop halal industry in Indonesia documentary video. The result is disseminated using open video sharing platform and already gathering attention from various individuals. We are hoping that we can help reducing islamophobia and also show the potential of halal industry to economics growth in Indonesia, especially to younger generations.